Lower Mass Bound on the W′ Mass via Neutrinoless Double Beta Decay in a 3-3-1 Model - A. C. O. Santos; P. Vasconcelos (Advances in High Energy Physics)
The discovery of neutrino masses has raised the importance of studies in the context of neutrinoless double beta decay (0νββ), which constitutes a landmark for lepton number violation (LNV). The standard interpretation is that the light massive neutrinos that we observed oscillating in terrestrial experiments mediate double beta decay. In the minimal 3-3-1 model (3-3-1M), object of our study, there is an additional contribution that stems from the mixing between a new charged vector boson, W′, and the Standard Model W boson. Even after setting this mixing to be very small, we show that tight constraints arise from the nonobservation of 0νββ. Indeed, we derive bounds on the mass of the W′ gauge boson that might exceed those from collider probes and most importantly push the scale of symmetry breaking beyond its validity, leading to an exclusion bound for the minimal 3-3-1 model.